Comparison of vascular complications between external iliac and internal iliac artery anastomosis of the donor renal artery in renal transplant recipients - G. Manoj Kumar; Sunil Ashok; J. Suresh Kumar (Urology Annals)
Introduction: The arterial anastomosis in renal transplantation is done either end-to-end to the internal iliac artery (IIA) or end-to-side to the external iliac artery (EIA). This retrospective study is to compare the vascular complications of these two techniques occurring in the immediate postoperative period. Materials and Methods: The data of 111 patients who underwent renal transplantation (live and deceased) were collected from the hospital records. Fifty-four (48.6%) had live donors, and 57 (51.4%) had deceased donors. Fifty (45%) patients had anastomosis to IIA alone, 57 (51.3%) to EIA alone, and 4 (3.6%) to both vessels. Age and sex of the recipient, cause of chronic kidney disease, side of the donor kidney, and number of donor renal arteries, presence of atherosclerotic changes on the recipient’s vessels, and presence of diabetes mellitus were noted. The details of the perioperative and postoperative vascular complications and the management of each one were recorded. Results: Nine patients had vascular complications, of which 5 (55.5%) patients had main vessel transplant renal artery thrombosis, 1 (11.1%) patient had accessory renal artery thrombosis, and 3 (33.3%) patients had transplant renal artery stenosis (TRAS). Out of the six cases of transplant renal artery thrombosis, 4 (66.6%) were seen in anastomosis with EIA. All 3 (100%) cases of TRAS were seen in anastomosis to the EIA. The vascular complications were not significantly associated with the type of anastomosis. Conclusion: On short-term follow-up, the incidence of vascular complications was not found to be significantly affected by the type of anastomosis.